EXOTIC PLANTS IN THE CIBODAS BOTANIC GARDENS REMNANT FOREST: INVENTORY AND CLUSTER ANALYSIS OF SEVERAL ENVIRONMENTAL FACTORS - Junaedi, Decky Indrawan (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2014)
Due to potential impact of invasive alien (exotic) species to the natural ecosystems, inventory of exotic species in the Cibodas Botanic Gardens (CBG) remnant forest area is an urgent need for CBG. Inventory of exotic species can assist gardens manager to set priorities and plan better responses for possible or existed invasive plants in the CBG remnants forest. The objectives of this study are to do inventory of the exotic species in the CBG remnant forest and to determine whether several environmental variables play role to the existence of exotic species in the CBG remnant forests. There are 26 exotic plant species Â (23 genera, 14 families) found and recorded from all four remnant forests in CBG. Cluster analysis of four environmental variables shows that clustering of environmental factors of exotic species correlates with the abundances of those exotic species. The relation between environmental factor clusters and the abundance of those exotics signify the role of environmental variables on the existence of exotic plant species. The information of exotic plant species in the remnants forest is the base information for gardens manager to manage exotic species in CBG remnants forest. The relation of several environmental factors with exotic species abundance could assist gardens manager to understand better the supportive and or suppressor factors of exotics in the CBG remnants forest. Further study on these species is needed to set priorities to decide which species should be treated first in order to minimize the impact of exotic plant species to native ecosystem of CBG.